(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
Artivism has become a central element of political change in Chile. In 2019, during the October Chilean social outbreak, performing arts were an important part of public expression. This paper explores the role of flash mob as a form of Artivism in Chile from an interdisciplinary approach combining literature from Theatre Studies and Studies of Social Movements. Albacan proposes that flash mob turn out to be performative acts that reconnect individuals with their community in a cooperative, creative and playful way. Flash mob challenges the street routine because happens in a short, specific interval of time. Probably the most emblematic Chilean flash mob was A rapist in your path created by the collective Las Tesis. The intervention, inspired by the work of renowned feminist Rita Segato to create a performance that would show rape not just as a crime against an individual woman, but as the expression of a larger social issue.